Evidencia de cambios clínicos y radiográficos en implantes oseointegrados de superficie maquinada y modificada, 3-12 meses de seguimiento (2006)
ABSTRACT: The aim of this study is to undertake a clinical and radiographic evaluation between two different patient groups: machined versus modified surface, to find out if there is statistically significant difference that support the use of implants with different surface properties. Sixty screw, external hex connection implants were examined: one group with 30 machined surface implants (SuperCAT®), and a second group with 30 implants with modified surface (RBM®), for restoring a single tooth. The surgical procedure was performed according with the manufacturer’s protocol. After six months the second phase surgery was performed and the temporary restoration was placed. At this point, the first radiographic evaluation was made. The Roos et al (1997) parameters were followed for the clinical and radiographic evaluation. A 100% of osseointegration was accomplished in both groups. The average marginal bone loss was 0.78 mm, without significant differences between the groups. All implants were reported as success grade 1, with no complications. There are not significant differences between the two groups of machined and modified implant surfaces for single tooth restoration.